NILAI-NILAI PENDIDIKAN DALAM SURAT AD DHUHA - Ari Abi Aufa (AL-AUFA: JURNAL PENDIDIKAN DAN KAJIAN KEISLAMAN, 2019)
This articel discuse about values educations in surah Ad Dhuha, Surat Ad Dhuha cannot use the results of the translation only or based on the final text. If the surah is understood using a literal translation or just a text from a verse, the results of the understanding obtained may be confused. Education values ​​in surah Ad dhuha we will find a lot in interpretations, in the discussion verse by verse then we will gain an understanding of the meaning contained in the surah ad dhuha, the educational values ​​that we can get as first, do not dissolve in worldly affairs because worldly affairs can defeat, secondly, the afterlife of pleasure is more important than world affairs and therefore do not get lost in temporary world life. Third, apply gentleness to orphans, do not act harshly even rebuke him, fourth, always remember the favors of God that have been given and do not associate partners.